Alone together : making an Asperger marriage work - Bentley, Katrin, 1960- (Jessica Kingsley Publishers, 2007)
'A really honest and accurate account of what it is like living in a relationship with a man who is affected by Asperger syndrome. There will be something in this book for any one living in such a relationship and it will provide an invaluable guide to professionals who wish to develop their understanding of Asperger relationships. Katrin describes very honestly both the ups and downs of living with her husband Gavin and shows the difference that awareness, understanding and commitment can m.